Anti-thrombin III and Heparin Clotting Times in Thrombosis and Atherosclerosis - O’Brien, J. R (Thrombosis and Haemostasis, 1974)
A survey of the literature shows that when whole blood clots thrombin is formed and there is a decrease in anti-thrombin III (Anti-Th. Ill) and an increase in heparin neutralizing activity (HNA) which is probably identical to platelet factor 4 derived from platelets. Many studies of atherosclerosis and of arterial and venous thrombosis using various tests thought to measure Anti-Th. Ill and HNA report a decrease in Anti-Th. Ill or an increase in HNA or both. We have measured both in patients with atherosclerosis and survivors of myocardial infarction. The HNA was increased and the serum anti-thrombic activity was decreased relative to controls and there was an inverse correlation between the two measurements. All this evidence suggests that some kind of mild chronic intravascular coagulation may occur in atherosclerosis. These changes could be related to the cause or the result of atherosclerosis.